A person among others? Older people’s understandings of their everyday life during the Covid-19 crisis (Sociologisk Forskning, 2021)
This article examines how older people make sense of their situation in calls to a helpline a few months into the Covid-19 pandemic. By drawing on the sociology of everyday life to analyse callers’ various understandings of the crisis, the article nuances current knowledge about older people’s situation. The thematic analysis shows that the callers make sense of the crisis linked to social relations on a personal, anonymous, and abstract level. The callers’ responses to challenges to their everyday routines – adjustment or critical evaluation – are connected to different approaches to trust: basic trust in a shared social reality with someone or regulating trust in a set of norms independent from that other. Whereas the calls demonstrate very few positive adjustments in personal relations, they show that anonymous and abstract relations serve as important resources for both maintaining and re-evaluating everyday life during a crisis. Although older people’s lack of secure personal relations during the pandemic points to vulnerability, their resourcefulness is apparent in their active engagement in important anonymous and abstract relations.
Keywords: Covid-19; crisis; older people; the sociology of everyday life; trust; Corona crisis